Analisis Dampak Pengeluaran Pemerintah Terhadap Indeks Pembangunan Manusia: Studi Empiris di Provinsi Jawa Barat - Andriani, Rahma; Elliott, Putri Destiani Nur; Prabowo, Rakhmat (Jurnal Pendidikan Ekonomi Indonesia, 2024)
Public development, especially in the education and health sectors, in West Java is often uneven, especially in remote areas, where education and health facilities are not yet fully adequate. Therefore, the aim of this research is to investigate the effect of government spending in the education and health sectors on increasing the Human Development Index in the region. HDI is an important indicator in measuring the social and economic development of an area. This research uses secondary data obtained from various sources covering the period of the last several years (2017 to 2022) in West Java. The method used in this research uses the GLS (Generalized Least Squares) approach with a fixed effect model. Based on the regression results, it was found that general allocation funds had a significant negative effect on HDI, while the realization of the government budget and GRDP had a significant effect on increasing the human development index